PROBLEMS AND IMPROVEMENT OF STATE REGULATION IN AGRICULTURE OF THE REPUBLIC OF KAZAKHSTAN - Oralbayeva Aizhan Kuantkanovna (Academic Journal of Physical and Chemical Sciences, 2020)
The article deals with modern problems of state regulation and development of agriculture in Kazakhstan, provides analytical information on the condition of state regulation, proposes measures to improve the state of agricultural production